Apakah Kecerdasan Emosional, Intelektual, Spiritual Berpengaruh Terhadap Tingkat Pemahaman Akuntansi Mahasiswa Jurusan Akuntansi? - Rimi Gusliana Mais; Sri Handoko Sakti; Tutty Nuryati; Thoriqoh Salsabila (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2024)
This research aims to examine the influence of emotional intelligence, intellectual intelligence, and spiritual intelligence on the level of understanding of accounting among several classes of students majoring in Accounting at private campuses in the East Jakarta area. This type of research is quantitative. The data collection technique uses a survey method using a questionnaire via Google Forms. The total sample obtained was 284 students as respondents. The criteria used in this research were accounting study program students class 2018-2022. Based on the discussion of research results, it shows that partially the emotional intelligence variable has no effect on the level of accounting understanding, while intellectual intelligence and spiritual intelligence have a positive and significant effect on the level of accounting understanding. The results of this research provide an implication for every teacher to pay attention to students' emotional intelligence so that they do not feel bored and fed up quickly in studying accounting and are lazy to try again if they fail in accounting courses. This means that if a student often feels quickly bored, fed up and does not want to try to learn from failures that occur, it is certain that the student's understanding of accounting lessons will not develop.